1994
DOI: 10.4315/0362-028x-57.10.908
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Degradation of Egg Yolk Cholesterol

Abstract: CONTENTS Page Abstract xiii Publications & Communications xv List of Abbreviations xvi List of Figures and Tables xviii CHAPTER 1 Literature Review Introduction 92 Preparation and Characterisation of COD 93 Specificity and Mode of Action of COD 94 Cofactors of Cholesterol Oxidase 96 Cholesterol Oxidation Byproducts 96 COD Activity and Cholesterol Assay 97Potential Application for Cholesterol Degradation 98 Results and Discussion 99 Effect of Time and Temperature 99 Effect of Concentration 105Cholesterol De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…This methodology has obtained very promising results, but despite its potential, it is not used a lot on the industrial level because of its high price. Other recent methodology described for this purpose includes the selective degradation of cholesterol in egg yolks using the enzyme cholesterol oxidase together with ultrasound [ 99 ] or using different species of microorganisms [ 100 , 101 , 102 , 103 ]. Alternatively, cholesterol can be removed from egg yolks using microbial degradation or by complexation with β-cyclodextrin, alone or inmobilized in chitosan beads [ 104 , 105 ], high metoxyl pectins [ 106 ], Streamline Phenyl ® resin [ 107 ] anionic chelating agent [ 108 ] or low-cholesterol liquid food oil [ 109 , 110 ], or by obtaining egg yolk granules [ 111 ].…”
Section: Eggs and Egg-based Products With Low Cholesterol And Satumentioning
confidence: 99%
“…This methodology has obtained very promising results, but despite its potential, it is not used a lot on the industrial level because of its high price. Other recent methodology described for this purpose includes the selective degradation of cholesterol in egg yolks using the enzyme cholesterol oxidase together with ultrasound [ 99 ] or using different species of microorganisms [ 100 , 101 , 102 , 103 ]. Alternatively, cholesterol can be removed from egg yolks using microbial degradation or by complexation with β-cyclodextrin, alone or inmobilized in chitosan beads [ 104 , 105 ], high metoxyl pectins [ 106 ], Streamline Phenyl ® resin [ 107 ] anionic chelating agent [ 108 ] or low-cholesterol liquid food oil [ 109 , 110 ], or by obtaining egg yolk granules [ 111 ].…”
Section: Eggs and Egg-based Products With Low Cholesterol And Satumentioning
confidence: 99%
“…Muconic acids can be produced by a strain of R. rhodochrous . Cholesterol oxidases from Rhodococcus have been studied and could have applications in the food industry or in steroid drugs' production (Finnerty 1992;Christodoulou et al 1994;Kreit et al 1994). Efficient production of the amino acids L-leucine and L-phenylalanine using Rhodococcus enzymes has been reported (Hummel et al 1987;Bhalla et al 1992).…”
Section: Other Applied Aspects Of Rhodococcusmentioning
confidence: 99%
“…It has been used for the determination of cholesterol in blood serum and in the production of the precursor for chemical synthesis of steroid hormones (Watanabe et al 1986;Lolekha et al 2004). Furthermore, various investigators have demonstrated the degradation of cholesterol and low density lipoprotein by CholOx and indicated that the use of CholOx may provide an economic and practical method for reducing the amount of dietary cholesterol (Aihara et al 1988;Christodoulou et al 1994;Wu et al 1995;Watanabe et al 1989a;Kim et al 2002), which is partially related to cardiovascular disease, and hence serves to improve human health (Kaunitz 1978).…”
Section: Introductionmentioning
confidence: 99%